PEMBUATAN LEM DARI KOMPON KARET ALAM UNTUK PEREKATAN BAHAN KULIT ATASAN SEPATU DAN BAHAN KARET - Suharyanto Suharyanto (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2017)
Gluing method is a method to merge leather upper with rubber materials using Shear method by gluing the material to one another in the opposite direction with compound adhesive. This research aims to get compound adhesive to glue leather upper and rubber material. Gluing factors include time, temperature, pressure, type of glue, and glued materials. Methods would ultimately determine the strong adhesion between the leather upper and rubber materials. Formula of rubber compound adhesive consists of natural rubber added with additive materials such as activator, accelerator, plasticizers, fillers, glue and sulfur vulcanizator, and then milled using two-roll mill to be a rubber compound, a solid brown color. Manufacture of compound adhesive with 100 grams of rubber, added with 70 grams petroleum solvent, for 24 hours. The next process is smearing leather upper in 8, 10, 12, 11, 14, and 16 minutes, with the highest test results of drying time is 16 minutes with the strong adhesion of 268.04 N. The strongest adhesion between leather upper and rubber material reach the highest drying time of 12 minutes with the strong adhesion of 149.06 N. In conclusion, adhesion between leather and leather are stronger than leather and rubber materials using Shear Test.